Disseminated Mycobacterium bovis Infection after BCG Vaccination - Shahla Afshar Paiman; Ahmad Siadati; Setareh Mamishi; Parviz Tabatabaie; and Ghamartaj Khotaee (Iranian Journal of Allergy, Asthma and Immunology, 2006)
The Calmette-Güerin vaccine (BCG) is administered to all the newborns in Iran in order to prevent tuberculosis. Complications of this vaccine are uncommon. We report disseminated BCG disease in 17 patients less than 10 years old. This is a retrospective study of total of 17 cases who were admitted in Children Medical Center Hospital with systemic syndrome compatible with Mycobacterium disease with evidence of histopathologic demonstration of acid-fast bacilli during 1995-2004. Fourteen cases occurred in children younger than 1 year old. Nine patients were female. Ten of the 17 total cases were associated with an immune deficiency including severe combined immunodeficiency, chronic granulomatous disease and cell mediated immune defect. Response to therapy was ineffective and 10 of them (58.8%) died. Disseminated BCG disease is an uncommon but devastating complication of vaccination that should be considered in the appropriate clinical setting. Immune-compromised infants are at greatest risk and they respond poorly to standard therapies.